Internet based teleoperation of autonomous underwater vehicle - Annamalai Sridevi (2008)
Autonomous Underwater Vehicles (AUV) are aquatic submersible with the ability to operate and carry out missions without manual inputs, tethers, or remote control. They must detect, interpret and effectively maneuver through their environment. The ability to perform such tasks makes and AUV an important tool for missions such as pipeline and cable inspection.